Interpersonal meaning in English and Vietnamese job advertisements: A systemic functional comparison. M.A Thesis Linguistics: 60 22 02 01 - Trần, Thị Bích Ngọc (University of Languages and International Studies, 2017)
The present thesis endeavors to make a contrastive analysis of the basic realization of interpersonal meaning in the discourse of English and Vietnamese job advertisements. A corpus of fifteen English job advertisements and fifteen Vietnamese ones are selected from the well-known English and Vietnamese recruitment websites at random to carry out the research work.